Plan de negocios para la creación de una agencia colocadora de empleos en la ciudad de Quevedo año 2012 - Macias Calero, Veronica Maria (2012)
The current reform of the Ministry of Labour Relations Ministry of Labor before emptied the body of his remaining limited capacity to help workers find jobs and has led to the emergence of agencies, entities in charge of mediating between workers and firms to try to hunt the supply and demand for labor. This research conducted a general analysis on local labor intermediation system, definitions and important considerations related to the topic. It took into account the characteristics and objectives of labor mediation, legal regulations in which the proposal is based, such as: Code Amendment Act of Labour, working patterns, and service regulations for hiring, strategic management of human resources in labor mediation. Within this context set out to answer the following research question: How can create a job placement agency in the city of Quevedo, to provide a specialized service in 2012? The general objective was raised for this research is: Create a Job Placement Agency in the city of Quevedo, to provide a specialized service in 2012, deriving its main specific objectives: that was developing a plan of operations to identify processes and resources, performing a market study to determine the demand for the service of a Job Placement Agency and developed a technical, economic and financial feasibility of determining the investment in creation of a Placement Agency Jobs. In this way and by hypothesis was evident if adequate market research related to the business of the agency setter jobs, provide opportunity to provide and cover the jobs required by the business sectors of the city of Quevedo, to from 2012. It should be noted that the research was based on a descriptive and applied research aimed at studying, analyzing, describing and if necessary change the reality of the present nature of the problem under study. Further research will support the use of techniques such as interviews and survey where information is sought and provided directly to draw conclusions from that no company engaged in placement activities of Quevedo Canton jobs , to spur the sector labor system and its environment and also determined that there is a great demand for this reason it was considered feasible to open the job placement agency in the city of Quevedo as the technical report and gives financial proposal is viable because it has all the necessary tools to implement the calculated values: NPV = $ 525,149; IRR = 219%, amounts are considered to justify the performance and feasibility of this project, which will serve the residents of Canton and to produce positive Quevedo socioeconomic progress thereof.